DIKLAT PEMBUATAN MEDIA PEMBELAJARAN BERBASIS WEB - Sabariah, Sabariah; Rufi’i, Rufi’i; Nurmida Chaterine Sitompul; Andri Kurniawan (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The "Web-Based Learning Media Development Training" organized by the MGMP of Economics and Chemistry in Sampang Regency aims to enhance teachers' competence in utilizing web technology for interactive learning. This training supports the improvement of digital learning quality in the Society 5.0 era through innovative and effective learning media design. The training follows the PAR approach, using media such as laptops, LCD projectors, and mobile phones. Results show that Google Sites development enriches content, Hypercontent boosts interactivity, and PowerPoint creates dynamic learning experiences. The training achieved an average score of 87.8, indicating successful implementation. Participant satisfaction was recorded at 4.6, showing very high satisfaction. In conclusion, the training was successful and effectively improved teachers' competence in using information technology to enhance teaching quality and student learning outcomes